The New Counter-insurgency Era in Critical Perspective - Ward Gventer, Celeste. author. aut Link
XIII, 375 p.
Keywords: The notion of counter-insurgency has become a dominant paradigm in American and British thinking about the wars in Iraq and Afghanistan. This volume brings together international academics and practitioners to evaluate the broader theoretical and historical factors that underpin COIN, providing a critical reappraisal of counter-insurgency thinking.